Hematology of common carp following DNA vaccination and koi herpesvirus challenge test - Sri Nuryati; N.A. Maswan; . Alimuddin; . Sukenda; K. Sumantadinata; F.H. Pasaribu; R.D. Soejoedono; A. Santika (Jurnal Akuakultur Indonesia)
The study was aimed to determine the effectiveness of DNA vaccine doses on hematological aspect which represent immune response and its influence on common carp survival rate. DNA vaccines encoding the viral glycoprotein of  koi herpesvirus (KHV) have been proved to highly protect the fish under laboratory condition.  A dose of 12.5 µg/100 µl vaccine had resulted in a survival rate of 96.67 % during 30 days after challenge test with a lethal dose of KHV. Fish vaccinated using lower doses, i.e. 2.5 and 7.5 µg/100µl showed 100% mortality after 15 and 19 days challenge test respectively, whereas non vaccinated fish as a control showed 100% mortality after 17 days challenge test.  Total leucocytes of the vaccinated fish were higher than control until 42 days post vaccination, but declined afterward.  Phagocytic index of the vaccinated fish using 12.5 µg/100 µl was declined after 49 days post vaccination or 7 days post challenge test.